Riffing on Feyerabend: Direct Observation, Paraconsistentist Logic, and a Research Immanent Account of the Rationaliy of Science - Couvalis, George (Filozoficzne Aspekty Genezy, 2024)
Feyerabend’s work, particularly his early papers contain important insights into the nature of science and scientific progress. I discuss his insights into the limits of empiricist foundationalism and positivism. I explain how the work of a number of philosophers has borne out Feyerabend’s claims in startling and interesting ways. Nevertheless, I criticise Feyerabend’s move from his attack on universal method to relativism. I point out that Feyerabend never confronted a well-developed research immanent view of the rationality of scientific change, which shows the limitations of the arguments in Against Method.